Adverse effects of In-Vitro cadmium exposure on quality and antioxidant enzyme status of Boar Spermatozoa (2014)
This study was aimed to evaluate the reproductive toxicity of cadmium chloride (CdCl2. 2.5H2O) in Boar spermatozoa in vitro. Boar spermatozoa obtained from the caudal epididymis of freshly slaughtered boars and dispersed in semen incubation medium (containing tris-hydroxymethyl-aminomethane, citric acid and fructose) were incubated at four different concentrations (0, 0.5, 1.0 and 2.0mM) for 3 hours at 370C. Sperm viability, motility and percentage of abnormal spermatozoa were assessed by microscopy every one hour during the 3–hour incubation period, using aliquots from the incubated samples. Samples thus treated with cadmium chloride were centrifuged and the supernatant was used in the assessment of biochemical parameters of oxidative stress including hydrogen peroxide (H2O2), reduced glutathione (GSH) and Lipid peroxidation. The activities of antioxidant enzymes, catalase (CAT), superoxide dismutase (SOD), Glutathione peroxidase (GPX) as well as transaminases (ALT and AST) and alkaline phosphatase (ALP) were also assessed. The percentage of motile and viable spermatozoa decreased significantly (p<0.05) after exposure of spermatozoa to CdCl2 in a concentration- and time-dependent manner. Cadmium significantly increased (p<0.05) the levels of H2O2 and malondialdehyde (MDA) in the spermatozoa with significant reductions (p<0.05) in the activities of SOD, GPX, and CAT. Slight but insignificant increase in GSH concentration was accompanied with a slight increase in GST activity. ALT, AST and ALP activities were differentially modified. The results of this study revealed that cadmium chloride caused reductions in sperm motility and viability, induction of oxidative stress and impairment of antioxidant enzyme activities.